ANALISIS PENETAPAN HARGA JUAL DENGAN METODE COST PLUS DAN METODE TINGKAT PENGEMBALIAN ATAS MODAL YANG DIGUNAKAN PADA TOKO MEBEL LESTARI PEJAGOAN - Kristanti, Ika Neni (Fokus Bisnis, 2013)
The selling price of a product is one element to be considered in deciding to buy consumer products. The cost factor used as a starting point in determining the selling price of the product. Cost plus method and the method of return on capital is one method of determining the selling price based on costs incurred by the company. The purpose of this study was to determine the selling price to cost plus method, method rate of return on capital employed, and find a suitable method for Toko Mebel Lestari. Methods of data collection method is observation, interview, documentation, and literature. Data analysis is to calculate all the cost data on Toko Mebel Lestari and insert selling prices formula. Based on Toko Mebel Lestari selling price per unit produced each month is different. Differences in the cost plus method because the amount of production per unit and fixed boarders. Method of return on capital because of the amount of production and the costs incurred each month. While the difference of the two methods because the return on capital and investment. The method is suitable for Toko Mebel Lestari is a method of cost plus method than the rate of return on capital. Key words : Determining the selling price, cost plus method, method rate of return on capital.